The footprint of cometary dust analogues – II. Morphology as a tracer of tensile strength and application to dust collection by the Rosetta spacecraft. Issue 3 (17th April 2019) - Ellerbroek, L E; Gundlach, B; Landeck, A; Dominik, C; Blum, J; Merouane, S; Hilchenbach, M; John, H; van Veen, H A
ABSTRACT: The structure of cometary dust is a tracer of growth processes in the formation of planetesimals. Instrumentation on board the Rosetta mission to comet 67P/Churyumov–Gerasimenko captured dust particles and analysed them in situ . However, these deposits are a product of a collision within the instrument. We conducted laboratory experiments with cometary dust analogues, simulating the collection process by Rosetta instruments (specifically COSIMA, MIDAS). In Paper I, we reported that velocity is a key driver in determining the appearance of deposits. Here in Paper II, we use materials with different monomer sizes, and study the effect of tensile strength on the appearance of deposits. We find that mass transfer efficiency increases from ∼1 up to ∼10 per cent with increasing monomer diameter from 0.3 to 1.5 $μ m$ (i.e. tensile strength decreasing from ∼12 to ∼3 kPa), and velocities increasing from 0.5 to 6 m s −1 . Also, the relative abundance of small fragments after impact is higher for material with higher tensile strength. The degeneracy between the effects of velocity and material strength may be lifted by performing a closer study of the deposits. This experimental method makes it possible to estimate the mass transfer efficiency in the COSIMA instrument. Extrapolating these results implies that more than half of the dust collected during the Rosetta mission has not been imaged. We analysed two COSIMA targets containing deposits from single collisions. The collision that occurred closest to perihelion passage led to more small fragments on the target.